SUSTAINABILITY OF SCHOOL-BASED FOOD AID IN BAHI DISTRICT OF TANZANIA'S DODOMA REGION AFTER THE END OF WORLD FOOD PROGRAMME SUPPORT - Joyce Exusper Nemes (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2018)
This study investigated the sustainability of school-based food drive after the phasing out of the World Food Programme (WFP) aid initiative in Bahi district of Dodoma region, Tanzania. The study found that none of the 72 public primary schools in Bahi district had managed to provide school lunch during the post-WFP by October 2017. Only 10 schools managed to provide porridge rather than full lunch to the pupils during the review period. The public primary schools under review were unable to sustain the School Food Programme due to the poor level of parental contributions, drought and widespread poverty. The study also found that parents complained about the school food programme lacking support within the national policy framework.  The study recommends the application of the Resource Dependency Theory to sustain the SFP and government's intervention to boost agricultural production and empower the people to support their wards and the SFP at their wards' school.